Influence of pre-operative refraction in LASIK surgery success - Rodrigues, Pedro Filipe (2018)
Introduction LASIK surgery is an essential technique for the correction of myopia and/or myopic astigmatism. Results are described to be better in myopia lower than -6.00D and in astigmatism higher than 1.00D.  Purpose To analyze the refractive characteristics that influence the surgical outcome of LASIK surgery. Material and Methods Retrospective study of consecutive cases of LASIK surgery performed to correct myopic error in Instituto de Oftalmologia Dr. Gama Pinto between 2010 and 2015. Results There were selected 392 eyes from 224 patients. The pre-operative spherical error varied between +1.75D and -9.00D (mean of -3.18D ±1.82), the cylindrical error varied between -0.25D and -6.00D (mean of -1.19D ±1.12) and the spherical equivalent varied between -0.38D and -9.38D (mean of -3.78D ±1.63). The mean uncorrected visual acuity after the surgery was 1,1 lines lower than the best corrected visual acuity, with a strong correlation between the sphere/spherical equivalent and the efficacy but with no correlation for astigmatism. Surgical success was achieved in 284 cases (72%). When comparing those with the cases without success, statistically significant differences were found between the groups, specifically concerning the sphere and spherical equivalent, without other significant differences. Grouping based on spherical equivalent confirmed statistically significant differences in surgical efficacy, mainly above -6.00D. Discussion Our results show an independent correlation between pre-operative refraction and surgical efficacy, especially regarding the sphere and spherical equivalent, which becomes particularly important in myopia higher than -6.00D.